PENGARUH PENERIMAAN DANA ZISWAF, NPF NETT, DAN PENDAPATAN MUSYARAKAH TERHADAP GWM DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI PADA PERBANKAN SYARIAH DI INDONESIA TAHUN 2018-2023 - Almuzayyad Almuzayyad; Eka Wahyu Hestya Budianto Budianto (Prodi. Hukum Ekonomi Syariah, Fakultas Syariah, IAI Hamzanwadi Pancor Lombok Timur, 2024)
This research aims to determine and examine the effect of ZISWAF Fund Receipts, NPF Nett, and Musyarakah Income on reserve requirements with Firm Size as a moderation variable. The sample used in this study is companies in the financial sector, namely Islamic banking in 2018-2023. The sampling technique used is purposive sampling, with a total sample of 5 companies for 5 years. The data analysis techniques used are Panel Data Regression Analysis and Moderated Regression Analysis (MRA) with the Eviews 12 application. The results of this study show that ZISWAF Fund Receipts show an influence on the Minimum Statutory Reserve (GWM). Likewise, NPF Nett shows an influence on the reserve requirement. Meanwhile, Musharakah Revenue does not show any influence on the Minimum Statutory Demand Deposit. Then, on the interaction of moderation variables, firm size cannot moderate the effect of NPF Nett on the financial sector's Minimum Statutory Current Account in 2018Q1-2023Q3. In addition, firm size is also unable to moderate the effect of ziswaf fund receipts and financial income on the financial sector's Minimum Statutory Current Account in 2018Q1-2023Q3. In future studies, it is expected to use other variables as variables that can become moderation variables. In addition, in the next study, it is recommended not only to look at companies from the financial sector, but also look at companies from other sectors so that the research results can also represent other business sectors. Keywords: ZISWAF funds, NPF Nett, Musyarakah Income, GWM, Company Size